Estimativa do consumo de água em lavoura orizícola com o uso de modelo plúvio-hidrométrico - MOPH - Acosta, Sandro Pedrotti (2004)
This study aimed to evaluate the applicability of the use of the rainflow model, in order to identify the water consumption to the irrigation, as an auxiliary tool on the water resources management. The area of this study was the Santa Maria River basin, which is a region with an intense rice culture. The model adopted on this work was the MOPH, developed by Silveira (1999). On this study was adjusted the parameters for each sub-basin from March up to October, which is the period without irrigation. With the adjusted parameters founded, was synthesized the flows for the period from November up to February, which is the period with irrigation. The supposition was that the difference between the synthesized flows on the irrigation period and the respective observed flows could indicate the consumption order of greatness. With the obtained results it was concluded that the presented model gets to translate that order of greatness, but it still requests studies that consider another variable as for instance the representation of the dams in the consumption of water in the farming of rice.